Indocyanine green‐enhanced multimodal photoacoustic microscopy and optical coherence tomography molecular imaging of choroidal neovascularization. Issue 5 (11th February 2021) - Nguyen, Van Phuc; Folz, Jeff; Li, Yanxiu; Henry, Jessica; Zhang, Wei; Qian, Thomas; Wang, Xueding; Paulus, Yannis M.
Abstract: Photoacoustic microscopy (PAM) has great potential for visualization of the microvasculature with high spatial resolution and contrast. Early detection and differentiation of newly developed blood vessels named choroidal neovascularization (CNV) from normal vasculature remains a challenge in ophthalmology. Exogenous contrast agents can assist with improving PAM sensitivity, leading to differentiation of CNV. Here, an FDA‐approved indocyanine green (ICG) was utilized as a PAM contrast agent. ICG was conjugated with RGD peptides, allowing the ICG to bind to the integrin expressed in CNV. Molecular PAM imaging showed that ICG‐RGD can target CNV for up to 5 days post intravenous administration in living rabbits with a model of CNV. The PAM image sensitivity and image contrast were significantly enhanced by 15‐fold at 24 h post‐injection. Overall, the presented approach demonstrates the possibility of targeted ICG to be employed in PAM molecular imaging, allowing more precise evaluation of neovascularization. Abstract : This study investigates the FDA‐approved indocyanine green (ICG) conjugated with RGD as a biocompatible fluorescent and photoacoustic microscopy (PAM) contrast agent for visualization of choroidal neovascularization (CNV). Intravenous ICG‐RGD was able to target CNV and enhance PA signal amplitude. ICG‐RGD multimodal molecular PAM, OCT and fluorescence imaging helped identify the margin and distinguish CNV. These results illustrate that ICG‐RGD demonstrates promise for multimodal imaging with high resolution and contrast.